Hyperspectral multi-indicator ripeness perception model for mechanized harvesting of “Yulu Xiang” pears - Na Ma; Jinyan Sun; Yingjun Li; Shijun Sun; Chenfei Li; Yile Sun; Zonglin Liu; Wendong Niu; Xiaoqin Xue; Haiyan Song (Computers and Electronics in Agriculture, 2026)

Competitive coordination-driven solvation sheath reconstruction in ternary eutectic electrolytes enables high-voltage fast-charging lithium metal batteries - Jiawei Chen; Zhen Wang; Youqian Chen; Wanrong Li; Lei Mao; Anjun Hu; Na Yang; Yong Xiang; Xiaobin Niu; Fei Li (Chemical Engineering Journal, 2026)

Integration of targeted metabolomics and volatilomics with electronic sensory technologies to reveal key components of Chinese white tea from five major production regions - Yuhang Zhang; Li Niu; Ruoxian Wang; Na Li; Juan Li; Mingzhi Zhu; Kunbo Wang (Food Chemistry, 2026)

Fe3O4-doped DCD-modified PAN-based nanofiber mat with synergistic photo-Fenton catalytic evaporation performance for multifaceted water treatment - Yifan Niu; Wenxin Wang; Mingzhe Zhao; Ning Wang; Martin Jensen; Na Han; Xianfeng Li (Journal of Environmental Chemical Engineering, 2026)

An active cling film developed from pomelo peel for synergistic preservation of Oncorhynchus mykiss: Utilizing K/Fe enzyme-like materials and natural extracts - Tao Yu; Long Cheng; Yini Zhao; Long Gu; Hangfei Gao; Zicen Liu; Li Huang; Shuyan Bai; Dongli Qin; Peng Wang; Aimin Wang; Haijiao Xie; et al. (Food Packaging and Shelf Life, 2026)

Identification of novel genes involved in pediatric congenital heart disease using trio-based whole genome sequencing - Bo Wang; Mo Li; Wei Zhou; Huiwen Chen; Ying Xiang; Guocheng Shi; Guoling You; Luan Chen; Yesheng Zhang; Xiaoqing Zhang; Yunqian Gao; Lulu Li; et al. (Science Bulletin, 2026)

Seasonal decoupling of water supply and CO2 fluxes of urban greening shrubs is driven by leaf area index - Wenxu Huang; Shaoning Li; Shaowei Lu; Na Zhao; Bin Li; Yuan Niu; Jiaying Li; Xiaotian Xu (Journal of Environmental Management, 2026)

Microwave-induced low-temperature treatment for efficiently removing PCDD/Fs from secondary copper smelting fly ash: key parameters, additive agents, and internal mechanism - Siyu Gong; Yifan Niu; Yongchao Yang; Jinhao Zheng; Na Li; Shaohua Ju; Hongbo Peng (Fuel, 2026)

Directing CH4 selectivity in CO2 photoreduction with Au nanoparticles electron mediation in Z-scheme WS2/g-C3N4 heterojunctions - Shicheng Liu; Jianghong Zhang; Jing Xiang Ng; Junbo Yu; Qulan Zhou; Na Li; Yanqing Niu (Chemical Engineering Journal, 2026)

Epithelial sodium channel in dendritic cells participates in high-fat-induced inflammatory responses - Xu Li; Shi-Li Zhou; Lin Bai; Chun-Lei Yu; Na Niu (Molecular Biology Reports, 2025)

Unveiling the gut-vascular connection: Gut microbiota regulates cardiovascular toxicity induced by combined exposure to PM2.5 and high-fat diet via butyric acid/NLRP3 pathway - Jiayu Tian; Jiaji Cheng; Huan Yang; Zeyu Niu; Lifang Zhao; Linlin Guan; Nannan Liu; Shuling Rong; Caihong Wang; Dongxing Shi; Huiqiu Zheng; Na Cao; et al. (Journal of Hazardous Materials, 2025)

PEDUNCLE LENGTH 1 regulates wheat peduncle elongation through brassinosteroid signaling pathway - Hong Liu; Liya Zhi; Hualiang Qiao; Yanxiao Niu; Jianxiu Shang; Hao Zhang; Wenzhao Xie; Yazhou Xuan; Wenqing Li; Jijie Li; Xinyu Zhang; Liuge Xue; et al. (Molecular Plant, 2025)

Engineered apoferritin-coumarin nanosensor for hyper-sensitive in vivo tracking of plant isoprene emissions - Xuejia Sun; Tingxi Han; Jiaxing Li; Qijun Sun; Chenglin Su; Shuang Cao; Boyuan Qiao; Jiating Xu; Na Niu; Ligang Chen (Chemical Engineering Journal, 2025)

Curvature-engineered hollow MoS2 nanoreactors boosted hydrodeoxygenation of lignin derivatives to arenes - Xinyong Diao; Chunyuan Zhang; Zuyi Zhang; Yawen Shi; Xinyi Niu; Shengbo Zhang; Hanyang Li; Na Ji (Chemical Engineering Journal, 2025)

Luteolin prevents axitinib-induced kidney damage in mice - Na Niu; Xu Li; Dong Tang; Tian-Qing Jin; Si-Wen Ji; Chun-Lei Yu; Yong Li (Chemico-Biological Interactions, 2025)

Zinc-releasing adhesive oral patch for prevention of radiation-induced oral ulcerative mucositis - Xiang Li; Kai-Yan Wang; Wen Qin; Wei-Wei Yu; Xin-Yi Hao; Wen Niu; Xu-Fang Liu; Qing Liu; Jian-Hua Wei; Yao Zhao; Franklin R. Tay; Ling-Yun Xia; et al. (Chemical Engineering Journal, 2025)

Development of corn straw lignin-based cling films for enhanced preservation of strawberries - Tao Yu; Tong Wang; Renguo Zhang; Chenglin Su; Shuang Cao; Yini Zhao; Hejing Wang; Jiaxing Li; Na Niu; Ligang Chen (Food Packaging and Shelf Life, 2025)

Studies on the synthesis, crystal structures, biological activities and molecular docking of novel natural methylxanthine derivatives containing piperazine moiety - Wenqi Fan; Shuyun Zhang; Na Yang; Yonghong Li; Xiao Zhang; Congwei Niu; Xinghai Liu; Baolei Wang (Molecular Diversity, 2025)

The association between estrogenic activity evolution and the formation of different products during the photochemical transformation of parabens in water - Xiaolin Niu; Guanhui Chen; Na Luo; Mei Wang; Mei Ma; Xinping Hui; Yanpeng Gao; Guiying Li; Taicheng An (Water Research, 2025)

Low loading palladium-carbon catalyst for efficient rosin disproportionation: Structure–activity relationship, reaction pathway, and catalytic dehydrogenation mechanism - Yifan Niu; Siyu Gong; Na Li; Xian Zhou; Shaohua Ju; Yongwan Gu (Fuel, 2025)

Amino-tuned S-scheme ZIF nano-heterojunction coating up/downconversion nanoparticles for near-infrared-triggered catalytic therapy and bioimaging - Chunsheng Li; Jiawei Qu; Yunlong Li; Shuang Liu; Zhengyang Tang; Qiang Wang; Jin Ye; Jiating Xu; Na Niu; Ligang Chen; Piaoping Yang (Chemical Engineering Journal, 2025)

Corrigendum to ‘A study of macroinvertebrate community structure and diversity in response to land use type in the Yiluo River Basin’ [Environ. Res. 255 (2024) 119157] - Na Zhao; Zhijun Yao; Weijun Chen; Chenxi Sang; Zhiwei Li; Xiaoli Niu; Feilong Gao (Environmental Research, 2025)

Hypertension toxicity of VEGFR-TKIs in cancer treatment: incidence, mechanisms, and management strategies - Yan-Xi Du; Xu Li; Si-Wen Ji; Na Niu (Archives of Toxicology, 2025)

Self-supporting CoFe2O4 nanoparticles on 2D g-C3N4/2D loofah activated carbon mediated peroxymonosulfate activation for tetracycline degradation - Beibei Niu; Wenjun Li; Na Geng; Shuaichen Li; Wangshu Tang; Xiaoxiao Zhang; Congshu Huang; Jianzhi Wang (Journal of Environmental Chemical Engineering, 2024)

A study of macroinvertebrate community structure and diversity in response to land use type in the Yiluo River Basin - Na Zhao; Zhijun Yao; Weijun Chen; Chenxi Sang; Zhiwei Li; Xiaoli Niu; Feilong Gao (Environmental Research, 2024)

MicroRNA-322-5p targeting Smurf2 regulates the TGF-β/Smad pathway to protect cardiac function and inhibit myocardial infarction - Liping Guo; Ke Li; Yan Ma; Huaiming Niu; Jun Li; Xin Shao; Na Li; Yuehui Sun; Haixiong Wang (Human Cell, 2024)

Intravenous immunoglobulin for treatment of hospitalized COVID-19 patients: an evidence mapping and meta-analysis - Mei-xuan Li; Yan-fei Li; Xin Xing; Jun-qiang Niu; Liang Yao; Meng-ying Lu; Ke Guo; Mi-na Ma; Xiao-tian Wu; Ning Ma; Dan Li; Zi-jun Li; et al. (Inflammopharmacology, 2024)

Characterization and fine mapping of a maize lesion mimic mutant (Les8) with enhanced resistance to Curvularia leaf spot and southern leaf blight - Jiankun Li; Tianyuan Fan; Ying Zhang; Ye Xing; Mengyao Chen; Ying Wang; Jie Gao; Na Zhang; Jinjun Tian; Chenyang Zhao; Sihan Zhen; Junjie Fu; et al. (Theoretical and Applied Genetics, 2024)

A critical review of environmental exposure, metabolic transformation, and the human health risks of synthetic musks - Na Luo; Yanpeng Gao; Xiaoyi Chen; Mei Wang; Xiaolin Niu; Guiying Li; Taicheng An (Critical Reviews in Environmental Science and Technology, 2023)

Performance and reaction mechanism of Mg-doped and Li-doped La2O3 catalysts in oxidative coupling of methane: DFT and experiment study - Na Sun; Jiayu Zhang; Lixia Ling; Pengyu Niu; Riguang Zhang; Litao Jia; Debao Li; Baojun Wang (Fuel, 2023)

Advances in Transformation Mechanism and Increased Adverse Effects of Pharmaceuticals and Personal Care Products During Environmental Geochemistry Processes - Yanpeng Gao; Xinyi Hu; Xiaolin Niu; Na Luo; Mei Wang; Yuemeng Ji; Guiying Li; Taicheng An (Reviews of Environmental Contamination and Toxicology, 2023)

Prevalence of paratuberculosis in cattle in China: A systematic review and meta-analysis - Na Lu; Ya-Ling Niu; Yang Song; Dan-Dan Zhang; Jing Jiang; Jiaqi Wei; Hong-Li Geng; Hongwei Cao (Preventive Veterinary Medicine, 2023)

Temporal patterns of algae in different urban lakes and their correlations with environmental variables in Xi'an, China - Shengnan Chen; Hanyan Liu; Haihan Zhang; Kai Li; Na Wang; Weimin Sun; Xiang Liu; Limin Niu; Ben Ma; Fan Yang; Haiyun Li; Daijuan Zhao; et al. (Journal of Environmental Sciences, 2023)

The unprecedented 2022 extreme summer heatwaves increased harmful cyanobacteria blooms - Na Li; Yunlin Zhang; Yibo Zhang; Kun Shi; Haiming Qian; Huayin Yang; Yongkang Niu; Boqiang Qin; Guangwei Zhu; R. Iestyn Woolway; Erik Jeppesen (Science of The Total Environment, 2023)

The immunomodulatory effects of DNA-conjugated collagen scaffolds on bone healing - Jing-han Song; Jun-ting Gu; Gao-peng Dang; Zhi-ting Li; Chen Lei; Ling Li; Zhao Mu; Franklin R. Tay; Kai Jiao; Li-na Niu (Chemical Engineering Journal, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Efficient cadmium immobilization by organic loaded Na-montmorillonite in a contaminated soil - Na Liu; Guoliang Niu; Liwen Xu; Jiaqi Wang; Chengliang Li; Yanli Liu (Science of The Total Environment, 2023)

Study on the effect of Ce–Cu doping on Mn/γ-Al2O3 catalyst for selective catalytic reduction in NO with NH3 - Wen Nie; Xiao Yan; Fengning Yu; Qiu Bao; Na Li; Weiwei Zhou; Wenjin Niu; Qifan Tian (Environmental Geochemistry and Health, 2023)

Biochars-Fe PCu hybrides deriving from solid waste and waste acids for elimination of refractory organic pollutants from pharmaceutical wastewater - Huiwen Jin; Li Li; Na Luo; Hongyun Niu; Jinglong Han; Lin Xu; Zhineng Hao; Dong Cao; Yaqi Cai (Chemical Engineering Journal, 2023)

N, O-diatomic dopants activate catalytic activity of 3D self-standing graphene carbon aerogel for long-cycle and high-efficiency Li-CO2 batteries - Wei Yu; Limin Liu; Yuxiao Yang; Na Li; Yuzhi Chen; Xiangkai Yin; Jinpen Niu; Jiuhong Wang; Shujiang Ding (Chemical Engineering Journal, 2023)

Upgrading the accumulation of ginsenoside Rd in Panax notoginseng by a novel glycosidase-producing endophytic fungus G11-7 - Lili Niu; Xiangyu Qin; Litao Wang; Na Guo; Hongyan Cao; Hanghang Li; Chunjian Zhao; Huimei Wang; Yujie Fu (Folia Microbiologica, 2023)

Removal of nitrate nitrogen from wastewater by green synthetic hydrophilic activated carbon supported sulfide modified nanoscale zerovalent Iron: Characterization, performance and mechanism - Shuaibing Fang; Jingxi Zhang; Yifan Niu; Shaohua Ju; Yongwan Gu; Kai Han; Xiaoxi Wan; Na Li; Yu Zhou (Chemical Engineering Journal, 2023)

A new bi-radical species formed during the photochemical degradation of synthetic musk tonalide in water: Study of in-situ laser flash photolysis and validation of synthesized standard sample - Na Luo; Yanpeng Gao; Mei Wang; Xiaolin Niu; Guiying Li; Taicheng An (Science of The Total Environment, 2023)

Temporal spectrum of spatial correlations between GNSS station position time series - Yujiao Niu; Paul Rebischung; Min Li; Na Wei; Chuang Shi; Zuheir Altamimi (Journal of Geodesy, 2023)

Methane supply drives prokaryotic community assembly and networks at cold seeps of the South China Sea - Mingyang Niu; Longhui Deng; Lei Su; S. Emil Ruff; Na Yang; Min Luo; Qi Qi; Jiangtao Li; Fengping Wang (Molecular Ecology, 2023)
Marine cold seeps are unique chemosynthetic habitats fuelled by deeply sourced hydrocarbon‐rich fluids discharged at the seafloor. Through oxidizing methane and other hydrocarbons, microorganisms inhabiting cold seeps supply subsurface‐derived energy to higher trophic levels, sustaining highly productive oases of life in the deep sea. Despite the central role of microbiota in mediating biogeochemical cycles, the factors that govern the assembly and network of prokaryotic communities in cold seeps remain poorly understood. Here we analysed the geochemical and microbiological profiles of 11 different sediment cores from two spatially distant cold seeps of the South China Sea. We show that prokaryotic communities belonging to the same methane‐supply regimes (high‐methane‐supply, low‐methane‐supply and non‐seep control sediments) had a highly similar community structure, regardless of geographical location, seep‐associated biota (mussel, clam, microbial mat) and sediment depth. Methane supply appeared to drive the niche partitioning of anaerobic methanotrophic archaea (ANME) at the regional scale, with ANME‐1 accounting for >60% sequence abundance of ANME in the high‐methane‐supply sediments, while ANME‐2 dominated (>90%) the low‐methane‐supply sediments. Increasing methane supply enhanced the contribution of environmental selection but lessened the contributions of dispersal limitation and drift to overall community assembly. High methane supply, moreover, promoted a more tightly connected, less stable prokaryotic network dominated by positive correlations. Together, these results provide a potentially new framework for understanding the niches and network interplay of prokaryotic communities across different methane seepage regimes in cold‐seep sediments.

Low-Level Environmental Per- and Polyfluoroalkyl Substances and Preterm Birth: A Nested Case–Control Study Among a Uyghur Population in Northwestern China - Bo-Yi Yang; Jianhua Wu; Xilong Niu; Chuanjiang He; Michael S. Bloom; Maihefuzaimu Abudoukade; Mairiyemu Abulizi; Aimin Xu; Beibei Li; Li Li; Xuemei Zhong; Qi-Zhen Wu; et al. (Exposure and Health, 2022)

Green surfactant-modified TiO2 nanoparticles doped with La-Cr bimetal for NOx removal - Wen Nie; Weiwei Zhou; Na Li; Yun Hua; Qiu Bao; Jiayi Yan; Mingyue Yuan; Cheng Guo; Fengning Yu; Wenjin Niu; Chengyi Liu (Environmental Science and Pollution Research, 2022)

Genistein Alleviates Oxidative Stress and Inflammation in the Hypothalamic Paraventricular Nucleus by Activating the Sirt1/Nrf2 Pathway in High Salt-Induced Hypertension - Li-Gang Niu; Na Sun; Kai-Li Liu; Qing Su; Jie Qi; Li-Yan Fu; Guo-Rui Xin; Yu-Ming Kang (Cardiovascular Toxicology, 2022)

MdMYB88/124 modulates apple tree microRNA biogenesis through post-transcription processing and/or transcription pathway - Chun-dong Niu; Huan-ran Shi; Zi-tong Zhang; Tian-le Fan; Huan Dang; Peng-xiang Chen; Yin-peng Xie; Cha-na Bao; Feng-wang Ma; Qing-mei Guan; Xue-wei Li (Acta Physiologiae Plantarum, 2022)

The Impact of Economic Development of the Guangdong-Hongkong-Macao Greater Bay Area on Air Pollution: Investigation Based on Remote Sensing Data of Nighttime Lights and Air Pollution - Xiaole Ji; Shaoxing Li; Na Jiang; Fei Wang; Liya Fan; Xiao Niu (Frontiers in Marine Science, 2022)
Whether the Guangdong-Hongkong-Macao Greater Bay Area (GBA) can achieve the goal of environmental protection at the same time as its rapid economic development is an important issue that deserves attention. In this paper, we obtained remote sensing data on air pollution including CO, NO 2 , SO 2 , PM 10 , PM 2.5 , and nighttime light data. We combined the remote sensing data with county-level economic statistics to study economic development and air pollution in the Guangdong-Hongkong-Macao GBA. Our research showed that the economic development in the Guangdong-Hongkong-Macao GBA significantly increased the emissions of NO 2 , PM 10 , and PM 2.5 and did not have significant effects on CO and SO 2 . We constructed an emission intensity indicator of pollutants per unit of luminance. We found that the unit emission intensity of four categories of pollutants, PM 10 , PM 2.5 , SO 2 , and CO, showed a significant decreasing trend in line with economic development. The emission intensity of NO 2 showed a trend of first decreasing and then increasing. The conclusion of this research illustrates that the emission intensity of pollutants per unit of luminosity in the Guangdong-Hongkong-Macao GBA is continuously reducing. The emission of pollutants will gradually change from slow growth to zero growth. However, the emission of NO 2 pollution should be an area of focus in achieving the dual goals of economic development and environmental protection.

Quantifying discrepancies in the three-dimensional seasonal variations between IGS station positions and load models - Yujiao Niu; Na Wei; Min Li; Paul Rebischung; Chuang Shi; Guo Chen (Journal of Geodesy, 2022)

Activation of Autophagy Ameliorates Age-Related Neurogenesis Decline and Neurodysfunction in Adult Mice - Na Yang; Xueqin Liu; Xiaojie Niu; Xiaoqiang Wang; Rong Jiang; Na Yuan; Jianrong Wang; Chengwu Zhang; Kah-Leong Lim; Li Lu (Stem Cell Reviews and Reports, 2022)

Assessment of BDS-3 terrestrial reference frame realized by broadcast ephemeris: comparison with GPS/Galileo - Guo Chen; Na Wei; Min Li; Qile Zhao; Yujiao Niu; Hongliang Cai; Yinan Meng (GPS Solutions, 2022)

Evaluation of the efficacy and safety of hydroxychloroquine in comparison with chloroquine in moderate and severe patients with COVID-19 - Qiuyu Li; Cheng Cui; Fei Xu; Jianping Zhao; Nan Li; Haichao Li; Tianbing Wang; Hua Zhang; Na Liu; Yudong Wei; Xiaoye Niu; Yan Xu; et al. (Science China Life Sciences, 2021)

PARP1 rs1136410 C/C genotype associated with an increased risk of esophageal cancer in smokers - Rongmiao Zhou; Yan Li; Na Wang; Chaoxu Niu; Xi Huang; Shiru Cao; Xiangran Huo (Molecular Biology Reports, 2021)

The utility of fusing multi-sensor data spatio-temporally in estimating grassland aboveground biomass in the three-river headwaters region of China - Na Zeng; Honglin He; Xiaoli Ren; Li Zhang; Yuan Zeng; Jiangwen Fan; Yuzhe Li; Zhongen Niu; Xiaobo Zhu; Qingqing Chang (International Journal of Remote Sensing, 2020)

Correction to: CCR2 and CCR5 promote diclofenac-induced hepatotoxicity in mice - Zhanke He; Guoquan Wei; Na Li; Mengwei Niu; Shenhai Gong; Guangyan Wu; Teng Wang; Yong Jiang; Peng Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Interactions between intercropped Avena sativa and Agropyron cristatum for nitrogen uptake - Min Liu; Huimin Li; Jingjing Song; Minghua Song; Na Qiao; Yuqiang Tian; Yanjie Liu; Haishan Niu (Plant and Soil, 2020)

CCR2 and CCR5 promote diclofenac-induced hepatotoxicity in mice - Zhanke He; Guoquan Wei; Na Li; Mengwei Niu; Shenhai Gong; Guangyan Wu; Teng Wang; Yong Jiang; Peng Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Occurrence and distribution characteristics of polybrominated diphenyl ethers (PBDEs) from a closed deca-BDE manufacturing factory in Jiangsu province, China - Nankun Li; Shan Niu; Xiaohui Wang; Yuan Li; Situ Na; Reti Hai; Tianwei Li (Journal of Soils and Sediments, 2018)

Special heterogeneous cytoplasm suppresses the expression of the gene producing multi-ovary in common wheat - Jialin Guo; Zheng Li; Gaisheng Zhang; Huali Tang; Qilu Song; Yulong Song; Shoucai Ma; Na Niu; Junwei Wang (Euphytica, 2017)

Loci and candidate gene identification for resistance to Phytophthora sojae via association analysis in soybean [Glycine max (L.) Merr.] - Lihong Li; Na Guo; Jingping Niu; Zili Wang; Xiaoxia Cui; Jutao Sun; Tuanjie Zhao; Han Xing (Molecular Genetics and Genomics, 2016)

Enhancement of Oral Bioavailability of Curcumin by a Novel Solid Dispersion System - Liandong Hu; Yanjing Shi; Jian Heng Li; Na Gao; Jing Ji; Feng Niu; Queting Chen; Xiaoning Yang; Shaocheng Wang (AAPS PharmSciTech, 2015)

Genetic association of the P-glycoprotein gene ABCB1 polymorphisms with the risk for steroid-induced osteonecrosis of the femoral head in Chinese population - Yanqiong Zhang; Xiangying Kong; Rongtian Wang; Shangzhu Li; Yanfang Niu; Liuluan Zhu; Weiheng Chen; Na LIN (Molecular Biology Reports, 2014)

Construction of EGFP-Labeling System for Visualizing the Infection Process of Xanthomonas axonopodis pv. citri in planta - Li-Ping Liu; Zi-Niu Deng; Jin-Wang Qu; Jia-Wen Yan; Vittoria Catara; Da-Zhi Li; Gui-You Long; Na Li (Current Microbiology, 2012)

IL-6 −174G>C polymorphism and cancer risk: a meta-analysis involving 29,377 cases and 37,739 controls - Bin Xu; Xiao-Bing Niu; Zi-Dun Wang; Wei Cheng; Na Tong; Yuan-Yuan Mi; Zhi-Chao Min; Jun Tao; Peng-Chao Li; Wei Zhang; Hong-Fei Wu; Zheng-Dong Zhang; et al. (Molecular Biology Reports, 2011)

Dichloroacetate (DCA) enhances tumor cell death in combination with oncolytic adenovirus armed with MDA-7/IL-24 - Lianli Xiao; Xin Li; Na Niu; Jing Qian; Guoliang Xie; Yigang Wang (Molecular and Cellular Biochemistry, 2010)

Death and proliferation of chondrocytes in the degraded mandibular condylar cartilage of rats induced by experimentally created disordered occlusion - Kai Jiao; Mei-Qing Wang; Li-Na Niu; Juan Dai; Shi-Bin Yu; Xiao-Dong Liu; Guo-Wei Wang (Apoptosis, 2009)